Aggregates in concrete - Alexander, Mark G; Mindess, Sidney (Modern concrete technology series (E. & F.N. Spon), 2005)
Bringing together in one volume the latest research and information, Aggregates in Concrete provides a comprehensive account of the selection and use of aggregates in concrete.